Health system resilience and health workforce capacities: Comparing health system responses during the COVID‐19 pandemic in six European countries. (22nd February 2022) - Burau, Viola; Falkenbach, Michelle; Neri, Stefano; Peckham, Stephen; Wallenburg, Iris; Kuhlmann, Ellen
Abstract: Background: The health workforce is a key component of any health system and the present crisis offers a unique opportunity to better understand its specific contribution to health system resilience. The literature acknowledges the importance of the health workforce, but there is little systematic knowledge about how the health workforce matters across different countries. Aims: We aim to analyse the adaptive, absorptive and transformative capacities of the health workforce during the first wave of the COVID‐19 pandemic in Europe (January‐May/June 2020), and to assess how health systems prerequisites influence these capacities. Materials and Methods: We selected countries according to different types of health systems and pandemic burdens. The analysis is based on short, descriptive country case studies, using written secondary and primary sources and expert information. Results and Discussion: Our analysis shows that in our countries, the health workforce drew on a wide range of capacities during the first wave of the pandemic. However, health systems prerequisites seemed to have little influence on the health workforce's specific combinations of capacities. Conclusion: This calls for a reconceptualisation of the institutional perquisites of health system resilience to fully grasp the health workforce contribution. Here, strengthening governance emerges as key to effective health system responses to the COVID‐19 crisis, as it integrates health professions as frontline workers and collective actors. Highlights: The health workforce contributes to health system resilience. Comparative analysis of adaptive, absorptive and transformative capacities. Health systems prerequisites have little influence on capacity combinations. Governance emerges as key to health system responses to the coronavirus disease‐2019 crisis.